Deployment of Solar Sails by Joule Effect: Thermal Analysis and Experimental Results - Gianluigi Bovesecchi; Sandra Corasaniti; Girolamo Costanza; Fabrizio Paolo Piferi; Maria Elisa Tata (Aerospace, 2020)
Space vehicles may be propelled by solar sails exploiting the radiation pressure coming from the sun and applied on their surfaces. This work deals with the adoption of Nickel-Titanium Shape Memory Alloy (SMA) elements in the sail deployment mechanism activated by the Joule Effect, i.e., using the same SMA elements as a resistance within suitable designed electrical circuits. Mathematical models were analyzed for the thermal analysis by implementing algorithms for the evaluation of the temperature trend depending on the design parameters. Several solar sail prototypes were built up and tested with different number, size, and arrangement of the SMA elements, as well as the type of the selected electrical circuit. The main parameters were discussed in the tested configurations and advantages discussed as well.